The lure of Neptune : German-Soviet naval collaboration and ambitions, 1919-1941 - Philbin, Tobias R. (Studies in maritime history., 1994)
Based on recently published Soviet documents, German archival sources, and the growing body of scholarship on both navies, The Lure of Neptune illuminates the collaborative yet competitive naval relationship that existed between Germany and Russia between World Wars I and II. Tobias Philbin charts the uneven evolution of the symbiosis that developed as both Stalin and Hitler sought to build fleets that exceeded their grasps. Philbin contends that the course of Russo-German naval relations offers both a window inter-war political climate of the two nations and a case study of how a hostile geopolitical environment can unite powers that possess mutually hostile doctrines. Philbin bridges the disciplines of German and Soviet naval and military history to uncover the lessons Germany and Russia learned from World War I. He reveals the ways in which the war affected their respective pursuit of naval supremacy, and he evaluates the influence their policies had on one another. Of particular interest, his study exposes Stalin's ambitions for naval superiority, his willingness to exchange long-term security for short-term advances, and his opinion of Hitler and German policies. Analyzing Russo-German naval relations in detail, Philbin scrutinizes Russia's exchange of oil and raw materials for German naval technology, Germany's establishment of Basis Nord on the Russian coast, Russo-German cooperation in merchant raider exploits, and the day-to-day interactions of Russia and German naval leaders. Philbin's findings underscore the synergy between Germany and Soviet naval policy during the 1920s and 1930s, the relatively intimate relationship pursued by the countries following the Hitler/Stalin pact, and the irreconcilable national objectives that ultimately thwarted their collaborative naval efforts. -- from page 4 of cover.